Analisis Beban Kerja Kognitif Siswa Sekolah Menengah Pertama pada Tugas Aritmetika Mental - Rifa Firdah Awanis; Siti Khabibah; Elly Matul Imah (LP. Ma'arif Janggan Magetan, 2023)
This study aims to describe the cognitive workload of students on mental arithmetic tasks. This study is a qualitative descriptive research. Data collection was conducted on students of Class VIII-C SMPN 1 Situbondo consisting of 32 students and taken 10 students as research subjects. Data collection techniques of this study were mental arithmetic tasks, NASA-TLX questionnaires, and interviews. The data collection instruments used were mental arithmetic task questions, NASA-TLX questionnaire rating sheets, and interview guidelines. 10 research subjects were selected based on the cognitive workload and mental arithmetic of students. The results of this study showed that 6.25% were in the category of very low cognitive workload, 12.5% were in the category of low cognitive workload, 25% were in the category of moderate cognitive workload, 43.75% were in the category of high cognitive workload, and 12.5% were in the category of very high cognitive workload. Subjects with very low cognitive workload did not experience stress or difficulty when solving mental arithmetic tasks. Subjects with low cognitive workload did not experience stress or difficulty when solving mental arithmetic tasks. Subjects with moderate cognitive workload experience slight difficulties when solving mental arithmetic tasks. Subjects with a high cognitive workload experience stress to the point of making the subject feel irritated when solving mental arithmetic tasks. Subjects with very high cognitive workload experienced stress to the point of making the subject feel irritated when solving mental arithmetic tasks.